Kelestarian Lingkungan dan Alam dalam Al Qur’an (Membaca Penafsiran Quraish Shihab terhadapat Surat Al-A’raf ayat 56 dan Ar Rum 51) - Azis, Abdul; Syafaat Fadilah, Yadi (Indonesian Proceedings and Annual Conference of Islamic Law And Sharia Economic (IPACILSE), 2023)
As Caliph fil Ardh, humans have a very important role in preserving and maintaining the environment and surrounding nature in order to protect the balance of living things and the universe. Thus, man as Caliph fil Ardh has a position only as an executor who continues this divine task within the scope of caring, governing and managing the earth. This article uses qualitative method research where the author has focused the problematic object into a research question. The next technique, namely conducting library research by understanding: the interpretation of Prf. Dr. Quraish Shihab in natural verses. The results of this study show that the environment and nature are an order in space that includes biotic and abiotic components where both have relationships and influence each other, including the role of humans as managers on earth (Khalifa fil Ardh). Obstacles: emerging potential damage both on land and at sea, for example environmental pollution and human arrogance that makes nature lose its function. Solutions that can be developed are by applying 4 principles of the concept of environmental and natural sustainability so that life and natural balance are maintained, safe, peaceful and provide benefits for all creatures.